THE DATA REVOLUTION IN B2B MARKETING STRATEGIES: EXPLORING THE POTENTIAL OF INNOVATION AND CAPABILITIES DEVELOPMENT IN THE DIGITAL ERA - M. Syafarudin Mahaputra; Ucu Supriatna; Zaenal Aripin (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
The Data Revolution has significantly influenced B2B marketing strategies in the digital era. This article explores the potential for innovation arising from the use of data in B2B marketing and how companies can develop their capabilities to take advantage of these opportunities. By leveraging data effectively, companies can unearth deeper insights into their customers' behavior and preferences, enabling them to develop more focused, personalized and responsive marketing strategies. The innovation potential includes greater personalization in marketing, development of more targeted marketing campaigns, responsive real-time marketing, and a more integrated and holistic approach to marketing. However, to take advantage of the potential of this innovation, companies must develop their capabilities to manage and analyze data wisely, and ensure that the use of their data is done ethically and in accordance with applicable privacy regulations. By doing this, B2B companies can position themselves to successfully capitalize on the opportunities offered by the Data Revolution and achieve competitive advantage in an increasingly connected and rapidly changing marketplace.